SAT0455 Subclinical Atherosclerosis and Estimation of Cardiovascular Risk in Systemic Sclerosis. (9th June 2015) - Ozen, G.; Korkmaz, F.; Sunbul, M.; Deniz, R.; Tigen, K.; Atagunduz, P.; Inanc, N.; Direskeneli, H.
Abstract : Background: During the last decade, it has been shown that cardiovascular disease (CVD) in systemic sclerosis (SSc) is increased and accounts for ∼30% of the SSc mortality. But, whether this is due to accelerated atherosclerosis and how to detect patients with high risk are still unclear. Objectives: To determine the frequency of subclinical atherosclerosis in patients with SSc compared to rheumatoid arthritis (RA) and to determine the ability of CV risk indices in detecting high risk SSc patients. Methods: Eighty one SSc patients (F/M=74/7; age 49.7±12.1 years, limited/diffuse=49/32) and 80 age-sex matched RA patients (F/M=73/7;age 50.1±10.5 years) without CVD were assessed. All patients were evaluated with carotid ultrasonography (US). Carotid intima-media thickness (cIMT) >0.90 mm and/or carotid plaques were used as the gold standard test for subclinical atherosclerosis and high CV risk (US+). Systematic Coronary Risk Evaluation (SCORE), QRisk II and 2013 American College of Cardiology/American Heart Association (ACC/AHA) 10-year atherosclerotic CV disease risk (ASCVD) indices were calculated. Results: Fifteen (18.5%) SSc and 19 (23.8%) RA patients had subclinical atherosclerosis ( P =0.41). The mean cIMT (mm) was also similar in both groups (0.67±0.15 vs 0.68±0.15, P =0.74). None of the CV risk factors in SSc patients were worse than RA patients except for lower HDL-chol levels (table 1 ), but total-chol/HDL-chol was similar (3.6±0.9 vs 3.5±1). When US+ and US- SSc patients were compared, it was observed that US+ SSc patients were older, had more pulmonary arterial hypertension (PAH), elevated ESR, HT and less immunsuppressive usage (Table 2 ). In multivariate analysis, age (OR=1.1, 95% CI [1.02-1.8], P =0.014), elevated ESR (OR=9.3, 95% CI [1.6-55.5], P =0.014) and PAH (OR=4.8, 95% CI [1.12-20.8], P =0.035) were independently associated with subclinical atherosclerosis. Concerning CVD risk indices, of the 15 US+ patients only 0, 1 (6.7%) and 3 (20%) patients were classified as high CV risk according to SCORE, QRisk II and ACC/AHA 10-year ASCVD risk, respectively. Conclusions: Subclinical atherosclerosis in SSc is as frequent as in RA in which accelarated atherosclerosis is clearly defined. Atherosclerosis in SSc is independently associated with age, elevated ESR and PAH. CV risk indices, SCORE, QRisk II and ACC/AHA 10-year ASCVD risk are considerably insufficient in SSc to detect patients with subclinical atherosclerosis. Disclosure of Interest: None declared